Performance analysis of solar panel energy utilization in coffee drying applications - Qori Zulia Rahma; Ariyano Ariyano; Farhan Ilham Wira Rohmat; Muhamad Husen; Danishwara Ardyansyach Riyadi (Jurnal Abmas, 2025)
Coffee farmers in Cimenyan Village face significant challenges in the post-harvest drying process due to high rainfall, which reduces quality and lowers income. This research aims to evaluate the performance of an IoT-based coffee-drying system powered by photovoltaic energy, using global solar atlas data. The designed system is a 2 kWp coffee dryer house, which was simulated to assess energy performance, drying efficiency, economic aspects, and environmental impact. The simulation results indicate that the photovoltaic system achieves conversion efficiencies of 80-88% under high irradiance. Drying efficiency reached 54% at an optimal temperature of 50°C, with a specific energy consumption of 0.4-0.6 kWh/kg of water evaporated, which is lower than conventional electric dryers that reach approximately 1.0 kWh/kg. From an economic standpoint, the investment payback period is estimated to be 1.5-3 years with a benefit-cost ratio of 1.4-1.5. Additionally, this system has the potential to reduce CO₂ emissions by 0.5-1.5 tons per year per unit. The system's ability to reduce operational costs, improve product quality, and support sustainable energy transitions in rural Indonesia. Although initial costs and limited technical skills may constrain farmer adoption, cooperative-level implementation, hybrid energy integration, and ongoing training offer promising avenues for future development.   Abstrak Petani kopi di Desa Cimenyan menghadapi tantangan besar dalam proses pengeringan pascapanen akibat tingginya curah hujan, yang menyebabkan penurunan kualitas dan berkurangnya pendapatan. Penelitian ini bertujuan untuk mengevaluasi kinerja sistem pengeringan kopi berbasis IoT yang didukung energi fotovltaik dengan memanfaatkan data global solar atlas. Sistem yang dirancang berupa rumah pengering kopi berkapasitas 2 kWp dan disimulasikan untuk menilai kinerja energi, efisiensi pengeringan, aspek ekonomi, serta dampak lingkungan. Hasil simulasi menunjukkan bahwa sistem fotovoltaik memiliki efisiensi konversi sebesar 80-88 % pada kondisi iradiasi tinggi. Efisiensi pengeringan mencapai 54 % pada suhu optimal 50 °C, dengan konsumsi energi spesifik sebesar 0,4-0,6 kWh/kg air yang diuapkan, lebih rendah dibandingkan pengering listrik konvensional yang mencapai sekitar 1,0 kWh/kg. Dari sisi ekonomi, periode pengembalian investasi diperkirakan 1,5-3 tahun dengan rasio manfaat-biaya sebesar 1,4-1,5. Selain itu, sistem ini berpotensi mengurangi emisi CO₂ sebesar 0,5-1,5 ton per tahun per unit. Kemampuan sistem dalam menekan biaya operasional ini, meningkatkan kualitas produk, serta mendukung transisi energi berkelanjutan di pedesaan Indonesia. Meskipun adopsi oleh petani dapat terkendala biaya awal dan keterampilan teknis, penerapan pada skala koperasi, integrasi energi hibrida, serta pelatihan berkelanjutan menawarkan potensi pengembangan yang menjanjikan di masa depan. Kata Kunci: energi bersih terjangkau; fotovoltaik; Internet of Things; ketahanan ekonomi; pertanian berkelanjutan